PENDUGAAN DAYA DUKUNG LOKASI WISATA UNTUK MENUNJANG PENGEMBANGAN PARIWISATA YANG BERKELANJUTAN DI PANTAI PAAL, KECAMATAN LIKUPANG TIMUR, KABUPATEN MINAHASA UTARA - Kapantow, Gene H. M.; Tarore, Melissa L. G.; Lumingkewas, Jelly R. D. (AGRI-SOSIOEKONOMI, 2022)
This study aimed to estimate the carrying capacity of Paal Beach tourist sites, East Likupang, one of the main tourist attractions in the Likupang Special Economic Zone (SEZ). This research was conducted from March to November 2021. The data used were primary data and secondary data. Primary data were collected at tourist sites, both from visitors and the Paal Beach management. Secondary data were obtained from tourism site managers and related agencies such as Â Statistics Indonesia Office, Tourism Office, and also gathered from various available documents. The results showed that the Physical Carrying Capacity (PCC) for Paal Beach was 2654 visitors per day, while the Real Carrying Capacity (RCC) and Effective Carrying Capacity (ECC) had the same value, which were 1843 visitors per day. The data showed that the number of visitors on weekdays, weekends and national holidays was still below the PCC. However, there was an ocassion where the number of visitors on a national holiday exceeded the RCC and the ECC.